FR1.1: Do Water, Energy and Food Policies in Support of Solar Irrigation Enable Gender Transformative Changes in South Asia? Evidence from Policy Analysis in Bangladesh and Nepal - Khadka, Manohara; Uprety, Labisha; Shrestha, Gitta; Mukherji, Aditi; Mitra, Archisman (International Water Management Institute, 2022)
Solar-powered irrigation pumps (SIPs) is emerging as a popular technology to address water, energy and climate change challenges in South Asia, while enhancing livelihoods and food security. SIPs are deemed to be woman friendly renewable energy technology (RETs) because of its design, operation systems, and safety. While gender dimensions of natural resources are well documented, to what extent do water, energy and food (WEF) policies, including policies to promote SIP technologies in the countries of South Asia conceptualize and operationalize gender equality and social inclusion (GESI) are not well understood. We draw on a gender transformative analysis approach and rank WEF policies on a continuum ranging from scale of 0-3 (denoting gender blind, gender aware, gender responsive and gender transformative). We deploy this method to review 37 WEF sectoral policies of Bangladesh and Nepal. We find that while national governments are committed to gender equality and women's advancement and enshrine these principles in their Constitution, these higher-level aspirational principles are not always translated to the WEF sector policies. We find that WEF policies are aware of the need to include GESI and social equity in sectoral programming, yet operational rules for implementation of these policies often fail to the challenge structural barriers that prevent women and marginalized groups from participating in and benefiting from WEF policies, including from deployment of SIP technologies. This calls for transformation not only in the project implementation, but also in the policymaking processes of the WEF sectors in the South Asia region.